Perceptions and intentions toward medical assistance in dying among Canadian medical students - Falconer, James; Couture, Félix; Demir, Koray K; Lang, Michael; Shefman, Zachary; Woo, Mark (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Medical assistance in dying (MAID) was legalized in Canada in 2016. As of July 2017, approximately 2149 patients have accessed MAID. There remains no national-level data on the perspectives of future physicians about MAID or its changing legal status. We provide evidence from a national survey of Canadian medical students about their opinions, intentions, and concerns about MAID. Methods From October 2016 to July 2017, we distributed an anonymous online survey to all students at 15 of Canada’s 17 medical schools. The survey collected data on respondent socio-demographic characteristics, features of their medical education, intentions for medical practice, and perspectives on MAID. We analyzed responses using univariate descriptive and stepwise multivariate logistic regression. Results In 1210 completed surveys, 71% of respondents reported being willing to provide MAID under a legal framework that permits it. Non-religious respondents reported greater willingness to participate in MAID than respondents of any religious affiliation (p < 0.001). Frequency of religious attendance was inversely associated with willingness to provide MAID (p < 0.001). Medical students born in Québec were more willing to provide MAID than respondents from other provinces (OR 2.21; p < 0.001). Age, sex, socioeconomic status, year of medical study, previous academic major, and rural/urban city of birth were not associated with willingness to provide MAID. Conclusion As the current class of medical students becomes the first cohort of new physicians to enter Canada’s changing medical and legal landscape around MAID, our findings inform the public debate by examining attributes associated with support or opposition to the practice.